2021
DOI: 10.1002/cam4.3900
|View full text |Cite
|
Sign up to set email alerts
|

A novel five‐gene signature predicts overall survival of patients with hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common public health challenges, worldwide. Because of molecular complexity and tumor heterogeneity, there are no effective predictive models for prognosis of HCC. This underlines the unmet need for accurate prognostic models for HCC. Analysis of GSE14520 data from gene omnibus (GEO) database identified multiple differentially expressed mRNAs (DEMs) between HCC and normal tissues. After randomly stratifying the patients into the training and testing groups, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…miR-147a is involved in the regulation of cancer malignancy ( Lee et al, 2021 ), and was previously proposed as a potential prognostic factor for non-small cell lung cancer ( Lu and Luan, 2019 ). miR-103a-3p has been reported to be associated with cisplatin resistance in non-small cell lung cancer ( Wang Z. et al, 2021 ), and docetaxel resistance in prostate cancer ( Yi et al, 2022 ). miR-103a was also reported as a new regulator of Wnt signaling pathway in colorectal carcinoma ( Fasihi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-147a is involved in the regulation of cancer malignancy ( Lee et al, 2021 ), and was previously proposed as a potential prognostic factor for non-small cell lung cancer ( Lu and Luan, 2019 ). miR-103a-3p has been reported to be associated with cisplatin resistance in non-small cell lung cancer ( Wang Z. et al, 2021 ), and docetaxel resistance in prostate cancer ( Yi et al, 2022 ). miR-103a was also reported as a new regulator of Wnt signaling pathway in colorectal carcinoma ( Fasihi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study based on bioinformatics reported that MITD1, involved in cell cycle regulation, can be employed as an independent predictive factor for individuals with HCC, and MITD1 expression is associated with clinicopathological characteristics and natural killer cell infiltration ( 16 ). Additionally, increasing findings using bioinformatics demonstrated that DEGs between HCC and neighboring non-malignant tissues were remarkably enriched in cell cycle pathway ( 17 - 19 ). Therefore, the utility of bioinformatics to study the function of cell cycle-linked genes in HCC pathogenesis is necessary for improving the therapeutic effect of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The Kaplan-Meier analysis revealed that our signature was still closely associated with worse survival regardless of these clinicopathological features of HCC (Figures 4C-F and Supplementary Figure 4A). To further assess the predictive efficacy of our signature on OS in HCC patients, we compared it with the other four published TCGA HCC signatures (23,(25)(26)(27). The ROC curves and time-dependent c-index proved that our signature was more accurate in prognosis prediction than the four published signatures (Figures 4G, H and Supplementary Figure 4B).…”
Section: Prognostic Value Of the Ferroptosis-associated Long Non-codi...mentioning
confidence: 92%